An Examination of the Relationship Between the Funded Status of Defined Benefit Pension Plans and the Financial Condition of Sponsoring Organizations – Public Vs Private Sector - Phillips, Janet F. (Journal of Accounting Ethics and Public Policy, 2022)
Defined benefit pension plans are a bedrock of the U.S. economy providing guaranteed payment streams at pre-established amounts. Results suggest public plans, sponsored by State and Local governments, and private plans, sponsored by public corporations, are unfunded. State plans were found to have the largest pension and unfunded pension liabilities. Examination of relationships between unfunded pension liabilities and fiscal or financial stability of sponsoring organizations suggests unfunded State pension plans are more likely to be sponsored by financially struggling sponsors measured by general obligation bond ratings. Local governments and Corporations with unfunded pension plans are less likely to be struggling financially. Fiscal distress of Local governments was measured by survival analysis. Corporation financial distress was quantified by a model designed to predict bankruptcy. Financially stable organizations failing to fund pension plans, in this case local governments and corporations, suggests a lack of social responsibility.
Keywords: Defined benefit pension plans; dept.acc; financial or fiscal distress; peer-reviewed; social responsibility; unfunded pension liabilities; ⛔ No DOI found

How to Handle Pressure to Act Unethically - Haylon, Lisa S.; Bishop, Carol C.; Boyle, Douglas M.; Hermanson, Dana R. (Management Accounting Quarterly, 2022)
It is likely that accountants will face pressure to act unethically during their careers. We offer 10 practical steps to help financial professionals prepare for and respond to the pressure to act unethically.
Num Pages: 1-9 Place: Montvale, United States
Keywords: Accounting; Business And Economics–Accounting; Business And Economics–Management; Business ethics; Compliance; Conformity; Decision making; Fraud; Management accountants; Personality; Professionals; dept.acc; peer-reviewed; ⛔ No DOI found